Love's Redeeming Work : the Anglican Quest for Holiness. - Rowell, Geoffrey (OUP Oxford, 2003)
There is a rich vein of writing within Anglican tradition that has helped to form the theology and spirituality of the contemporary church. For many readers, much of this material remains unfamiliar and is often difficult to access. Love's Redeeming Work draws together the works of major writers from the sixteenth century to the present day who have contributed to this development. Each selected writer is introduced with a brief biography, which gives background information about the author, and highlights the relationships that existed with others from the same period. This will enable the rea.